Antiviral treatment in patients with advanced hepatitis C virus cirrhosis with sofosbuvir and either ledipasvir or daclatasvir, with or without ribavirin: observational cohort study. (25th February 2016) - Cheung, Michelle; Foster, Graham; Irving, William; McLauchlan, John; Walker, Alex; Hudson, Benjamin; Verma, Suman; Agarwal, Kosh
Abstract: Background: Direct acting antivirals (DAAs) successfully clear hepatitis C virus (HCV) infection without the use of interferon, allowing treatment of patients with advanced liver disease. Since April 2014, the Expanded Access Program (EAP) in England has provided DAAs for patients with advanced HCV cirrhosis—namely, sofosbuvir with ledipasvir or daclatasvir. We aimed to study the effectiveness of DAAs in advanced HCV cirrhosis, and to see whether viral clearance results in early liver function change. Methods: We included patients with advanced HCV liver disease fulfilling NHS England EAP criteria, who received 12 weeks of sofosbuvir and either ledipasvir or daclatasvir, with or without ribavirin (clinicians were free to choose the regimen). Patients were enrolled in the HCV Research UK database, and they consented to prospective data collection between April 1, 2014 (start of EAP), and Nov 11, 2014. A control group of patients with untreated HCV advanced cirrhosis was selected retrospectively between Oct 5, 2012, and Sept 11, 2014 (at least 6 months before EAP start), from the same database. Outcomes were sustained virological response (HCV RNA <30 IU/mL) 12 weeks after the end of treatment (SVR12), change in MELD (Model for End-Stage Liver Disease) score between baseline and 12 weeks after end of treatment, and serious adverse events including primary liver cancer, sepsis, or death within 6 months of treatment. Findings: Our cohort consisted of 467 treated patients (mainly HCV genotype 1 [n=231] and genotype 3 [n=192] infections) and 261 controls. 409 (88%) of 467 patients had past or present decompensation, and median MELD score was 11 (predicted 3 month mortality 6%). Significantly more patients with genotype 1 than genotype 3 infection achieved SVR12 (209 [91%] vs 132 [69%], p<0·0001), but not for ribavirin-containing compared with ribavirin-free regimens. High body-mass index and detectable virus at treatment week 2 were associated with lower SVR. MELD scores improved in treated patients (mean change −0·85) but worsened in untreated patients (mean change +0·75) (p<0·0001) within 6 months. Fewer treated patients than controls had decompensation events (18% [72/409] vs 28% [73/261], p=0·0006). All-cause adverse outcomes (MELD increase ≥ 2 and any serious adverse event) were reduced (52% [214/409] vs 64% [166/261], p=0·004) but there was no significant difference in incidence of primary liver cancer, sepsis, or death. Interpretation: High viral response rates were achieved with 12 weeks of treatment with DAAs in this large real-life patient cohort with advanced cirrhosis, who previously had limited treatment options. Patients with genotype 3 disease remain difficult to cure with existing regimens. That HCV treatment was associated with early improvements in liver function is clinically relevant in a population with poor prognosis. The longer-term impact of HCV treatment in patients with advanced cirrhosis needs to be determined. Funding: NHS England, Gilead, Bristol-Myers Squibb, HCV Research UK.